Aesthetic quality assessment of landscapes as a model for urban forest areas: a systematic literature review - Mundher, Riyadh; Abu Bakar, Shamsul; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Al-Sharaa, Ammar; Aziz, Azlizam; Gao, Hangyu (Multidisciplinary Digital Publishing Institute, 2022)
Aesthetic experience in a forest can typically be associated with attractive forest scenery that gives people a sense of visual pleasure. Characterized as a visual product based on people’s reactions towards various combinations of landscape settings, features, and objects, this type of natural visual pleasure may benefit people’s well-being, promotes natural and cultural heritage preservation, and encourages the growth of the eco-tourism industry. While most research on forest aesthetics focuses on non-urban settings, this study examines aesthetics in the context of urban forests. This study aims to systematically review landscape aesthetic assessment studies to propose a model for urban forests. We conducted a systematic review of research articles published from 2014 to 2020 by using three research journal databases, Science Direct, Scopus, and MDPI. In total, 55 research articles were identified and qualified for review based on the screening requirements. An additional 26 research articles were also included by using the snowball method to provide better understanding and outcomes for the study. The results were organized into these categories: definitions, benefits, philosophies, approaches, and variables for the aesthetic quality assessment in urban forest areas. In addition, we also found that aesthetic quality in urban forests is highly influenced by visual composition, visual sense, and visual conditions, which have also been proven to be important parts of forest functions and values that could contribute towards the preservation of urban green spaces.